Pedagogical Shift in Education During COVID-19 Pandemic: An SLR Approach - Janga Bahadur Hamal,; Narayan Prasad Aryal, (Interdisciplinary Journal of Management and Social Sciences, 2022)
This paper aims to examine the shift in modality of pedagogical approach of education during the COVID-19 pandemic and identify the challenges faced by educational institutions, teachers, student and parents, and the perception of students towards the approaches. The study is based on Systematic Literature Review (SLR) approach based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The study critically analyzed the findings of 27 research articles. The result depicted that COVID-19 pandemic had a significant impact on education due to which majority of the institutions shifted to online mode of teaching and learning. The shift was observed in both practical and theoretical studies, and also in schools who refrained from adopting digital technology prior to COVID-19 pandemic. There were numerous challenges faced by the educational institutions, such as, lack of technology, technical know-how, and experience in virtual teaching, among others. Similarly, parents felt burdensome to additional cost incurred for gadgets and internet. The study also revealed that despite the difficulties, students were positive about online teaching and learning, and thus the use of virtual methods of teaching with high inclusion of digital technologies ca be considered as best alternative for future considerations in academia.